South American herbal extracts reduce food intake through modulation of gastrointestinal hormones in overweight and obese women - Celestino, Marina Monteiro; Gomes, Aline Corado; Botelho, Patricia Borges; Gambero, Alessandra; Mesquita, Leonardo Mendes [UNESP]; Vilegas, Wagner [UNESP]; Ribeiro, Marcelo Lima; Mota, Joao Felipe (Elsevier B.V., 2017)
Herbal plants have been assessed for possible action that influence gastrointestinal hormonal secretion, modifying gut motility, food intake and energy balance. The effects of herbal extracts derived from native species of South America on food intake and acylated ghrelin and glucagon-like peptide 1 (GLP-1) concentrations after consuming meals were investigated for the first time in humans. Twenty overweight and obese women were recruited for a randomized, single blind, placebo -controlled, crossover design study separated by a 7-day washout period. Participants received an herbal extract combination containing yerba mate, guarana and damiana ('YGD') or placebo. Energy intake at lunch was reduced significantly in the YGD group (-43.3 +/- 13.1 kcal; P = 0.005). The AUC for acylated ghrelin after lunch was significantly lower in the YGD group (-1004 +/- 690.9 vs. 565.9 +/- 286.7, P = 0.04). At 60 and 150 min after breakfast, GLP-1 concentrations were higher in YGD (P = 0.04) when compared with the control group. The AUC for GLP-1 after breakfast was significantly higher in the YGD group (1003 +/- 370.5 vs. 160.3 +/- 221.3, P < 0.05). Supplementation with the herbal extract YGD reduced energy and macronutrient intake by modulating the gut hormones in overweight and obese women. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Obesity; Glucagon-like peptide 1; Ghrelin; Yerba mate; Guarana; Damiana